Skene's Gland Derivatives in the Female Genital Tract and Cervical Adenoid Basal Carcinoma are Consistently Positive With Prostatic Marker NKX3.1. (July 2021) - Hawari, Rand; Fernandes, Larissa; Park, Kay J.; McCluggage, W. Glenn
Abstract : Cervical ectopic prostatic tissue and vaginal tubulosquamous polyp are rare lesions which exhibit variable, and often focal, immunohistochemical expression with traditional prostatic markers [prostate-specific antigen and prostatic acid phosphatase (PSAP)]. These lesions are thought to arise from periurethral Skene's glands, the female equivalent of prostatic glands in the male. Adenoid basal carcinoma is a rare and indolent cervical neoplasm. Expression of the prostatic marker NKX3.1 in ectopic prostatic tissue and tubulosquamous polyp has been reported but no studies have examined immunoreactivity with this marker in adenoid basal carcinoma. We stained 19 cases [adenoid basal carcinoma (n=6), cervical ectopic prostatic tissue (n=11), and vaginal tubulosquamous polyp (n=3); 1 case contained both adenoid basal carcinoma and ectopic prostatic tissue] with NKX3.1. In all cases, the glandular component of these lesions exhibited diffuse nuclear immunoreactivity while normal endocervical glands were negative. Prostate-specific antigen was positive in 4 of 9 and 0 of 3 cases of ectopic prostatic tissue and tubulosquamous polyp, respectively, while PSAP was positive in 3 of 4 and 2 of 2 cases of ectopic prostatic tissue and tubulosquamous polyp respectively; 3 of 5 cases of adenoid basal carcinoma tested were focally positive with PSAP and all 5 were negative with prostate-specific antigen. While the specificity of NKX3.1 should be investigated in future studies, positivity with this marker may be useful in diagnosing these uncommon lesions. NKX3.1 appears a more sensitive marker of ectopic prostatic tissue and tubulosquamous polyp than traditional prostatic markers and positive staining provides further support that these lesions exhibit "prostatic" differentiation and are of Skene's gland origin. NKX3.1 and PSAP positivity in adenoid basal carcinoma raises the possibility of an association with benign glandular lesions exhibiting prostatic differentiation and we critically discuss the possible association.